Toxicological Evaluation of Five Herbal Drugs Hawked In Minna, Niger State - Kelechi E. Okunji, Musa Galadima and Ali A. Jigam (Journal of Applied Pharmaceutical Science)
The medicinal and cultural acceptance of herbal drugs has been established since ancient time but often without any toxicological assessment. In the present study the toxicological assessment of five herbal medicinal concoctions sold in Minna, Nigeria was carried out in mice. Parameters determined included weight variations, packed cell volume (PCV), total serum protein, glucose and triacylglycerides which were compared to control groups that were administered 20ml/kg body weight of normal saline. Phytochemical analysis revealed the presence of alkaloids, tannins, glycosides and flavonoids in most of the drugs. Safe doses of the drugs in the rodents were determined to range between 150-800mg/Kg body weight while LD50 were in the range of 800-2500mg/Kg body weight. Serum glucose, total proteins and triglycerides were each significantly (p
Keywords: Herbal,Concoctions,toxic,Adverse effects.